Severe Cherubism Treated with Curettage, Osteotomy, and Bony Repositioning: A Case Series of Three Patients. Issue 1 (27th January 2022) - Moss, Whitney; Pires, Giovanna; Zahid, Rehan; Tyrell, Richard; Rhemtulla, Irfan; Gociman, Barbu
Abstract : Summary: Cherubism is a rare, autosomal dominant condition characterized by the replacement of medullary bone by fibro-osseous lesions, predominantly in the bilateral maxillae and/or mandibles. The clinical presentation of cherubism can vary widely, from clinically undetectable to severe facial disfigurement. Although there are no established management guidelines for this condition, conservative management with observation is typically favored in most cases due to the possibility of spontaneous regression following puberty. In this article, we present three cases of moderate to severe cherubism managed with early surgical intervention utilizing curettage and osteotomy followed by bony repositioning. We aimed to show the feasibility and safety of this minimally invasive surgical technique in the management of moderate to severe cases of cherubism to provide improvement in patient quality of life, aesthetics, and function while also possibly mitigating the need for later reconstructive surgery.